Remarkable Natural Biological Resource of Algae for Medical Applications - Dai, Na; Wang, Qiang; Xu, Baisheng; Chen, Hui (Frontiers in Marine Science, 2022)
With increasing consumer awareness of the use of natural products in pharmaceuticals and medicine, it is noted that algae can be considered an appropriate source. Algae produce many bioactive components, which have application potential in pharmaceutical industries, such as fatty acids, phycobiliprotein, polysaccharides, phenolic compounds, carotenoids, and so on. However, it is still a long way before the truly widespread application of algae in medicine, and some research and technical bottlenecks still need to be resolved for further practical use. Here, we provide an in-depth review of the current understanding of algal-based medical application, with a focus on the main pharmaceutical activity and current application stage including in vitro, animal, and clinical studies. Furthermore, we propose some possible solutions to the obstacles that should be overcome for achieving the practical applications of algal-based medicine. Notably, animal and clinical studies on algal drugs and treatments should continue to push forward and expand for promoting the practical applications. Moreover, the developments in interdisciplinary research of algal biology and other disciplines provide new insight for driving algae-based medical application.